Aggregates of Small Nuclear Ribonucleic Acids (snRNAs) in Alzheimer's Disease - Hales, Chadwick M. (John Wiley and Sons Inc., 2014)
We recently discovered that protein components of the ribonucleic acid (RNA) spliceosome form cytoplasmic aggregates in Alzheimer's disease (AD) brain, resulting in widespread changes in RNA splicing. However, the involvement of small nuclear RNAs (snRNAs), also key components of the spliceosome complex, in the pathology of AD remains unknown. Using immunohistochemical staining of post‐mortem human brain and spinal cord, we identified cytoplasmic tangle‐shaped aggregates of snRNA in both sporadic and familial AD cases but not in aged controls or other neurodegenerative disorders. Immunofluorescence using antibodies reactive with the 2,2,7‐trimethylguanosine cap of snRNAs and transmission electron microscopy demonstrated snRNA localization with tau and paired helical filaments, the main component of neurofibrillary tangles. Quantitative real‐time polymerase chain reaction (PCR) showed U1 snRNA accumulation in the insoluble fraction of AD brains whereas other U snRNAs were not enriched. In combination with our previous results, these findings demonstrate that aggregates of U1 snRNA and U1 small nuclear ribonucleoproteins represent a new pathological hallmark of AD.